The Encounters of Clinical Teaching in Hierarchical and Collectivistic Contexts - Suhoyo, Yoyo (Springer Nature, 2022)
The socio-hierarchical context brings many consequences to student-centered learning, not only in the classrooms but also in clinical settings. The ideal observation-based learning may not work as expected during workplace-based clinical education and patient-care services. The ultimate summative assessment, which will be discussed in another chapter, will drive students' motivation to pass the final clinical examination as if it is the only way to succeed in their clinical education. Therefore, clinical learning likely lacks dialogue, supervision, observation, and feedback. Constructive comments are rare, as well as self-reflection, participatory learning, and initiatives. Using an experience-based learning model as the concept for clinical teaching in the 21st century, we discuss the difficulties and challenges of the country with collectivist and large power distance cultures. To implement the concept of clinical teaching in this cultural context medical teachers should be aware of tension between precondition for implementing the concept and cultural countries characteristics. In a collectivistic culture, serial discussions should be taken to reduce this tension while keeping the underlying ideal clinical teaching. We shared our experience in implementing innovation to improve clinical teaching in a hierarchical and collectivistic cultural context. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2022, corrected publication 2022.